Student Motivation In Learning Corner In Face To Face Is Limited - Riski; Oki Candra (CV. AFDIFAL MAJU BERKAH, 2022)
This research was conducted with the aim of finding out how much motivation students have when learning PJOK during the Coronavirus Disease 2019 (Covid-19) at SMAN 1 Pangkalan Kerinci. Coronavirus Disease 2019 (Covid-19) at SMAN 1 kerinci base. This research is a descriptive method with a survey type using a questionnaire as an instrument. Descriptive research is research conducted to describe certain symptoms, phenomena or events. Data collection is carried out to obtain information related to certain phenomena, conditions or variables and does not intend to test hypotheses. The population in this study were all class X students of SMAN 1 Pangkalan Kerinci, totaling 133 for the 2022 academic year. In this study, the total sampling technique was used for taking the sample. The samples in this study were all students at SMAN 1 Pangkalan Kerinci, totaling 133. The results of the study show that the motivation of Pangkalan Kerinci 1 Public High School students in participating in limited face-to-face PJOK online learning for the 2022/2023 academic year is in the very high category (7%) 9 students, high category with a percentage of (28%) 37 students, medium category with a percentage (38%) of 50 students, low category with a percentage (18%) of 24 students, very low category with a percentage (10%) of 13 students. It was concluded that the category of students at SMAN 1 Pangkalan Kerinci was in the medium category.